Is radioiodine necessary for patients with low-risk differentiated thyroid cancer after thyroidectomy: a pooled analysis of ESTIMABL2 and IoN trials - Yang, Chuansheng; Luo, Deping; Xie, Jian; Zou, Yingting; Chen, Fei; Yang, Wenchun; Zeng, Linfeng; Liu, Jing (Frontiers in Oncology, 2025)
BackgroundThe clinical utility of postoperative radioiodine therapy in patients with low-risk differentiated thyroid cancer (DTC) remains a subject of ongoing debate. Although radioiodine has been widely employed to reduce the risk of recurrence, its necessity in low-risk populations is increasingly questioned, given the favorable outcomes observed with surgery alone. To address this issue, we conducted a meta-analysis exclusively based on randomized controlled trials (RCTs) to comprehensively evaluate the efficacy and safety of radioiodine therapy in this specific patient population.MethodsWe systematically searched 6 databases for eligible phase 3 RCTs comparing surgery with or without radioiodine in patients with low-risk DTC. Primary outcomes included recurrence and recurrence-free survival (RFS); secondary outcomes included adverse events (AEs), structural events, and biological events. Risk ratios (RRs) or hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled and analyzed.ResultsTwo phase 3 RCTs (the ESTIMABL2 and IoN trials), encompassing 1280 patients, were included. Compared to the non-radioiodine group, radioiodine therapy did not significantly reduce recurrence rates (RR: 0.78 [0.36-1.70], P = 0.53) or improve RFS (HR: 0.96 [0.80-1.15], P = 0.68). The total number of structural events (RR: 0.83 [0.68-1.02], P = 0.07) and biological events (RR: 0.88 [0.71-1.08], P = 0.23) were also similar between the two groups. In the safety analysis, the two groups exhibited comparable rates of AEs (RR: 0.97 [0.79-1.20], P = 0.80), grade 3–5 AEs (RR: 0.25 [0.03-2.20], P = 0.21), death (RR: 1.28 [0.48-3.41], P = 0.62), and second primary cancers (RR: 1.26 [0.58-2.73], P = 0.55).ConclusionRadioiodine therapy did not confer significant benefits in reducing recurrence or improving RFS in patients with low-risk DTC after thyroidectomy, and the safety profiles were comparable between the two groups.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251105509.